2020
DOI: 10.1371/journal.pone.0236564
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 RNA by direct RT-qPCR on nasopharyngeal specimens without extraction of viral RNA

Abstract: To circumvent the limited availability of RNA extraction reagents, we aimed to develop a protocol for direct RT-qPCR to detect SARS-CoV-2 in nasopharyngeal swabs without RNA extraction. Nasopharyngeal specimens positive for SARS-CoV-2 and other coronaviruses collected in universal viral transport (UVT) medium were pre-processed by several commercial and laboratory-developed methods and tested by RT-qPCR assays without RNA extraction using different RT-qPCR master mixes. The results were compared to that of sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 14 publications
2
75
0
Order By: Relevance
“…Moreover, commonly used swab collection solutions may inhibit RT-PCR. Indeed, while several groups have demonstrated RNA amplification by direct addition of swab samples in the widely used viral transport medium (VTM), inhibition of RT-PCR by VTM typically leads to a significant delay in amplification [ 10 15 ]. A comparison of commercial master mixes found that the commonly used TaqPath master mix is particularly susceptible to inhibition by VTM [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, commonly used swab collection solutions may inhibit RT-PCR. Indeed, while several groups have demonstrated RNA amplification by direct addition of swab samples in the widely used viral transport medium (VTM), inhibition of RT-PCR by VTM typically leads to a significant delay in amplification [ 10 15 ]. A comparison of commercial master mixes found that the commonly used TaqPath master mix is particularly susceptible to inhibition by VTM [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…An ideal swab collection solution would be widely available or cheaply made in any laboratory, allow for sensitive, direct detection of patient swabs, and not require specialized storage conditions. Proposed swab collection solutions include saline [ 18 ], PBS [ 14 ], TE [ 24 ], or simply distilled water [ 15 , 18 ]. Also, addition of proteinase K (PK) to UTM or saline was reported to improve detection of viral RNA by direct addition [ 19 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other direct RT-PCR tests, saliva was diluted with a buffer and heated at 95 C for 30 min and then supplemented with Tween-20 [7] or heated at 65 C for 10 min [8]; an aliquot of the heat-treated, diluted sample was used for direct RT-PCR. The LOD for these tests, evaluated using saliva spiked with γ-irradiated SARS-CoV-2, was 1,000 copies of SARS-CoV-2 virus per ml of saliva [7], or 6,600 per ml of a viral suspension spiked with synthetic SARS-CoV-2 RNA [8]. Another direct RT-PCR test for detecting SARS-CoV-2 RNA used saliva treated with dithiothreitol (Sputasol) and a ribonuclease inhibitor [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, commonly used swab collection solutions may inhibit RT-PCR. Indeed, while several groups have demonstrated RNA amplification by direct addition of swab samples in the widely used viral transport medium (VTM), inhibition of RT-PCR by VTM typically leads to a significant delay in amplification [10][11][12][13][14][15]. A comparison of commercial master mixes found that the commonly used TaqPath master mix is particularly susceptible to inhibition by VTM [16].…”
Section: Introductionmentioning
confidence: 99%